Design and manufacture of tracking & tracing information system for tractor units using qr code technology at PT. Panca Traktor Indonesia - Winata, Wilson; Sharyanto, Sharyanto; Gunawan Sudarsono, Bernadus (Journal of Engineering, Technology and Computing (JETCom), 2024)
PT Panca Traktor Indonesia is a company that focuses on sales and service. Currently, PT Panca Traktor Indonesia still does not have a computerized system related to tracking and tracing tractor units, so customers do not know when the goods are delivered and where the goods are. Delivery is only via short message applications such as whatsapp and via telephone. In addition, there is no report on tracking and tracing related to shipments so that there is no data record. Therefore, to handle these problems, a tracking & tracing application using web-based QR code technology was created, which was designed and modeled using Unifield Modeling Langueage (UML), PHP as a programming language and MySQL as a database. With this application, it is expected to facilitate companies and customers in tracking and tracing tractor units.